Fringe Benefits in Tax Law: Matching Principle and Tax Justice Perspective - Heriantonius Silalahi; Budi Kurnia (Yayasan Ilomata, 2023)
This study addresses a significant issue within Indonesia's income tax policy, focusing on the taxation of fringe benefits and non-monetary compensations. Fringe benefits, being non-monetary rewards granted to employees, have gained prominence in various sectors' remuneration structures. The evolving landscape of in-kind taxation, encompassing natural elements, prompts inquiries into the determinants of tax imposition choices and their equity ramifications. The study aims to explore the income tax perspective on fringe benefits and non-monetary gains, emphasizing the applicability of the matching principle and its implications for equitable taxation. Despite the rising importance of fringe benefits, scholarly discourse on the alignment of conformity principles with in-kind taxes remains sparse. Therefore, this study offers a fresh contribution in comprehending this matter. Employing both a policy analysis and taxation approach, the study draws data from literature, tax statutes, and the latest economic reports. The findings underscore the significance of integrating the conformity principle in the taxation of fringe benefits and non-monetary rewards. This integration can augment the efficiency and transparency of state financial management, curbing detrimental tax avoidance practices that undercut state revenue. In summary, this study validates that adopting the conformity principle in taxing fringe benefits and non-monetary gains holds the potential to bolster state revenue and enhance fiscal management efficiency. The research's implications can guide policy makers in refining the national tax framework and fostering equitable taxation in Indonesia.